Space-time acupuncture for intractable cough after lupus nephropathy: A case report and literature review. Issue 51 (December 2017) - Guo, Taipin; Chen, Zukun; Tai, Xiantao; Liu, Zili; Zhu, Miansheng
Abstract: Rationale: Some intractable chronic cough remains a common complaint for seeking medical care. Unexplained cough in lupus nephropathy patient is rare and therapeutic options are limited. Patient concerns: A 57 year-old woman with a 7-year history of lupus nephropathy. She has suffered from chronic cough for 3 years accompanied with chronic low back pain and fatigue, as the conventional therapy cannot relieve the symptoms. Diagnoses: The woman is diagnosed as intractable cough after lupus nephropathy. Interventions: 9 times space-time acupuncture (STA) treatment was performed. Outcomes: The cough, as well as other uncomfortable symptoms like chronic low-back pain and fatigue have resolved, and no relapse for one year follow-up. Lessons: STA may be an effective therapy to treat intractable chronic cough.